Coordinated transcriptional regulation of the carotenoid biosynthesis contributes to fruit lycopene content in high-lycopene tomato genotypes. Issue 1 (1st June 2022) - Duduit, James R; Kosentka, Pawel Z; Miller, Morgan A; Blanco-Ulate, Barbara; Lenucci, Marcello S; Panthee, Dilip R; Perkins-Veazie, Penelope; Liu, Wusheng
Abstract: Lycopene content in tomato fruit is largely under genetic control and varies greatly among genotypes. Continued improvement of lycopene content in elite varieties with conventional breeding has become challenging, in part because little is known about the underlying molecular mechanisms in high-lycopene tomatoes (HLYs). We collected 42 HLYs with different genetic backgrounds worldwide. High-performance liquid chromatography (HPLC) analysis revealed lycopene contents differed among the positive control wild tomato Solanum pimpinellifolium, HLYs, the normal lycopene cultivar "Moneymaker", and the non-lycopene cultivar NC 1Y at the pink and red ripe stages. Real-time RT-PCR analysis of expression of the 25 carotenoid biosynthesis pathway genes of each genotype showed a significantly higher expression in nine upstream genes ( GGPPS1, GGPPS2, GGPPS3, TPT1, SSU II, PSY2, ZDS, CrtISO and CrtISO-L1 but not the well-studied PSY1, PDS and Z-ISO ) at the breaker and/or red ripe stages in HLYs compared to Moneymaker, indicating a higher metabolic flux flow into carotenoid biosynthesis pathway in HLYs. Further conversion of lycopene to carotenes may be prevented via the two downstream genes ( β-LCY2 and ε-LCY ), which had low-abundance transcripts at either or both stages. Additionally, the significantly higher expression of four downstream genes ( BCH1, ZEP, VDE, and CYP97C11 ) at either or both ripeness stages leads to significantly lower fruit lycopene content in HLYs than in the wild tomato. This is the first systematic investigation of the role of the complete pathway genes in regulating fruit lycopene biosynthesis across many HLYs, and enables tomato breeding and gene editing for increased fruit lycopene content.